Peran Guru Pak Membentuk Kepribadian Peserta Didik Melalui Keteladanan Yesus (1 Petrus 2 : 21) Terhadap Tantangan Zaman (Studi kasus kelas VIII SMP Negeri 2 Satu Atap Pantai Cermin) - Nurliani Siregar; Mita Patri Wika Habayahan; Ruth Ningsih Nababan; Romulus Sirait; Tamara Yulina Gultom; Christoper Sodipta Manik; Daslya Inaltria Munthe; Anita Yohana Anita Yohana Manurung; Incarini Siagian (Journal on Education, 2024)
In the context of globalization and technological developments today, various challenges must be faced by students to build a strong personality. This research aims to explain the role of Christian Religious Education (PAK) teachers in shaping students' personalities through the example of Jesus, inspired by the Bible text 1 Peter 2:21, to face the challenges of today's times. Through an approach using observational qualitative research methods, researchers directly interact with the school and students in the classroom learning process by teaching material that matches the title of the research. It is hoped that the research results will provide a deeper understanding of how the role of PAK teachers and the example of Jesus can influence the formation of students' personalities in facing the challenges of the times.